Evaluating Risk Factors for Lethality in Posterior Reversible Encephalopathy Syndrome following Hematopoietic Stem Cell Transplantation in Pediatric Patients: A Systematic Review and Individual Participant Data Meta-analysis - Padooiy Nooshabadi, Mohammadreza; Akbarnataj Bishe, Hossein; Ahmadi, Seyyed Amir Yasin; Eshagh, Marzieh; Behfar, Maryam; Jafari, Leila; Ali Hamidieh, Amir (Neuropediatrics, 2025)
Hematopoietic stem cell transplantation (HSCT) is frequently the sole curative treatment for a range of hematologic and nonhematologic disorders. One of the most notable neurological complications associated with HSCT is posterior reversible encephalopathy syndrome (PRES), which affects approximately 1 to 10% of pediatric recipients. Although usually reversible, PRES can lead to serious morbidity and lethality. This systematic review and individual participant data (IPD) meta-analysis aims to evaluate risk factors for lethality and characterize the clinical course of PRES in pediatric HSCT patients. Studies reporting PRES in pediatric HSCT recipients with data on outcomes and risk factors were included. Data were sourced from PubMed, Web of Science, Scopus, and Embase (last search: October 20, 2024). IPD were extracted from articles or requested from corresponding authors. Risk of bias was assessed using the Newcastle–Ottawa Scale. A one-stage IPD meta-analysis evaluated associations between risk factors and lethality and descriptive analyses reported the clinical course of PRES in the included population. Among 175 pediatric patients with PRES across 15 studies, the mean age was 8.68 years, and 64.8% were male. PRES occurred on average 73.08 days post-HSCT presenting with seizures (90.3%), hypertension (87.8%), altered mental status (31.9%), headache (28.5%), visual disturbances (27.1%), and atypical presentations (24.3%). Neuroimaging findings indicated that 12.3% of cases involved only anterior or posterior brain circulation, while most (75.4%) demonstrated dual circulation involvement, with bilateral cerebral involvement observed in 89.8% of patients. The overall lethality rate was 32.5%. The meta-analysis reported an overall prevalence of 7% for PRES among pediatric recipients of HSCT. The IPD meta-analysis revealed no significant associations between lethality and factors such as age (p = 0.590), sex (p = 0.516), atypical PRES presentations (p = 0.642), or the specific cerebral circulation involved (p = 0.758). Conversely, acute graft-versus-host disease demonstrated a trend toward statistical significance for association with lethality (p = 0.056). Additionally, underlying malignant disease (odds ratio [OR]: 2.635, 95% confidence interval [95% CI]: 1.256–5.529, p = 0.01), the use of cord blood as a cell source (OR: 5.692, 95% CI: 1.241–26.109, p = 0.025), and transplantation from an unrelated donor (OR: 4.948, 95% CI: 2.176–11.249, p < 0.001) were significantly associated with increased lethality risk. Malignant underlying disease, cord blood transplantation, and unrelated donors significantly increase lethality risk in pediatric HSCT recipients with PRES. These findings underscore the importance of tailored management strategies to identify and monitor at-risk pediatric HSCT recipients.
Keywords: posterior reversible encephalopathy syndrome; hematopoietic stem cell transplantation; pediatric recipients; posttransplant complications; treatment-related neurologic complications; risk factors for lethality